Vocabulary in the New B.Ed. General English under Tribhuvan University - Luitel, Binod (Journal of NELTA, 2012)
This paper reports a study on the curricular policy direction regarding vocabulary instruction, and the characteristics of words focused in the course books of General English for B.Ed. under Tribhuvan University. The research aimed at linguistic analysis of items, their frequency in general use, their usefulness considering the students’ career prospect, and the nature of their occurrence in course materials. The focus offered to vocabulary component in the course is found reasonably high; frequent vocabulary items focused for learning in the books are more than infrequent ones; and about two-thirds of the focused words are useful while the remaining one-third are not so useful for students. Out of the two course books used for vocabulary teaching, ‘Academic Vocabulary in Use’ has offered much more appropriate lexical content than ‘New Generation English’. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6130 NELTA 2011; 16(1-2): 59-69